A Proposed Approach For Solving Asymmetric Travelling Salesman Problem by Fuzzy Ant Colony Optimization Algorithm - Mehmet Aksaraylı; Osman Pala (Journal of Transportation and Logistics)
Logistics sector is one of the most prominent field in economic development of a country. Travelling Salesman Problem which is studied commonly in logistic sector is also based a number of other problems. Shortly, it is aimed to travel along to n locations with limitation of only visiting each location once. Due to NP-hard nature of problem, it is becoming impossible to find exact solution when the number of locations are above a certain level. Due to this reason, heuristic methods are mainly used for solving Travelling Salesman Problem. Ant Colony Optimization Algorithm which is a heuristic method that uses swarm intelligence gives good solutions in solving combinatorial optimization problems. In this study, Ant System and Ant Colony System are tested according to proposed principal of well distributed initial locations and different values of parameters for solving asymmetric Travelling Salesman Problem. Test problem which is in literature is solved by program that is coded in MATLAB programming language. Statistical analysis which is conducted on results indicate that proposed approach provides significant contribution on solutions.